2015
DOI: 10.1371/journal.pone.0136876
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Extreme Wind Conditions for Power at Coastal Locations in China

Abstract: In this paper, the normal and extreme wind conditions for power at 12 coastal locations along China’s coastline were investigated. For this purpose, the daily meteorological data measured at the standard 10-m height above ground for periods of 40–62 years are statistically analyzed. The East Asian Monsoon that affects almost China’s entire coastal region is considered as the leading factor determining wind energy resources. For most stations, the mean wind speed is higher in winter and lower in summer. Meanwhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In our study, most residents identified television as the main ways to get information before typhoon (83.5%), the result was similar with previous studies in China [ 14 , 28 ], Florida [ 26 ], and New Jersey [ 34 ]. TV is a major and convenient source of information among rural residents.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, most residents identified television as the main ways to get information before typhoon (83.5%), the result was similar with previous studies in China [ 14 , 28 ], Florida [ 26 ], and New Jersey [ 34 ]. TV is a major and convenient source of information among rural residents.…”
Section: Discussionsupporting
confidence: 91%
“…Among the southeastern regions of China, Zhejiang province is one of the very high-risk provinces most frequently affected by typhoons [ 28 ]. Super Typhoon “Chan-hom” landed in the middle coast of Zhejiang Province in July 2015, affecting 1.9 million people with a direct economic loss of almost 6 billion RMB, forcing 1.06 million people to evacuate [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rationale behind selecting the wind speed was to imitate light breeze conditions at sea. Moreover, calm (0 m/s) and extreme (13.375 m/s) wind speeds have been considered to assess dispersion behavior of smoke as recommended by Gao et al The wind direction in the current study was from the forward to the aft of the FLNG. The simulation time was 5 minutes.…”
Section: Proposed Methodology and A Case Studymentioning
confidence: 99%
“…Samples using wind speed statistics can be obtained from (21). After using the sample distribution to fit the theoretical distribution, a scientific and objective method is needed to check whether the actual overall distribution of the wind speed data conforms to the theoretical distribution.…”
Section: Optimal Criterion Of Estimationmentioning
confidence: 99%
“…For areas without long-term wind speed data, it is of great significance to provide a reasonable basic wind pressure for design reference based on limited short-term wind speed data. Currently, based on short-term wind speed data, scholars [20,21] use the annual and monthly maximum wind speed data as samples to calculate the wind pressure during the design reference period, but there are relatively few studies using the weekly and daily maximum wind speed data as sample for calculation, and there is a lack of research using both data calculate the basic wind pressure. Meanwhile, most of the existing studies are based on short-term wind speed data to focus on a certain city or region, but the rules summarized according to a certain region or city are not necessarily suitable for every region.…”
Section: Introductionmentioning
confidence: 99%